Be aware when heat shocking ascospores from crisp mutants of Neurospora crassa - H Cathcart; S N Bennett; W A Krissinger (Fungal Genetics Reports, 2002)
This laboratory has been working with a new crisp mutant of Neurospora crassa, crisp-5 isolated in our laboratory by Charlene Jackson (Jackson, 1992 MS Thesis: 1-123) by ultraviolet irradiation.